2005
DOI: 10.1007/s11240-005-9017-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of haploid and doubled haploid plants from pollinated ovaries of maize (Zea mays)

Abstract: Haploid induction has potential application for maize breeding. This paper reports that maize haploid plants have been induced by in vitro culture of pollinated ovaries. From a total of 26,400 cultured ovaries, 24 haploid plants were obtained and two of them were doubled after colchicine treatment. The maximum frequency of gynogenesis was 0.17% at 19.5 h post-pollination (HPP). The results showed that HPP was an important factor affecting plant induction from ovaries. Regenerated diploid R 0 plants were then s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…Plant regeneration via ovary culture has also been reported in several plants such as lily (Van Tuyl et al 1991), sweet potato (Ruth et al 1993), onion (Bohanec et al 1995, Luthar andBohanec 1999), sugar beet (Gurel et al 2000), maize (Tang et al 2006), coconut (Perera et al 2007) and Psoralea corylifolia (Chand and Sahrawat 2007). Although the main objective of the above studies, including the present study, was to obtain haploid plants; regeneration of diploid plants revealed the potential use of ovary explants for adventitious shoot proliferation.…”
mentioning
confidence: 95%
“…Plant regeneration via ovary culture has also been reported in several plants such as lily (Van Tuyl et al 1991), sweet potato (Ruth et al 1993), onion (Bohanec et al 1995, Luthar andBohanec 1999), sugar beet (Gurel et al 2000), maize (Tang et al 2006), coconut (Perera et al 2007) and Psoralea corylifolia (Chand and Sahrawat 2007). Although the main objective of the above studies, including the present study, was to obtain haploid plants; regeneration of diploid plants revealed the potential use of ovary explants for adventitious shoot proliferation.…”
mentioning
confidence: 95%
“…This technique is the female equivalent of the process described in the paragraph above, and has been applied to species including sugar beet [55,56], onion [57,58], squash [59], gerbera [60], rice [61], maize [62], niger [63] and tea [64]. Ovules have also been used as a transformation target [39].…”
Section: Ovule Culturementioning
confidence: 99%
“…Development of haploids by biotechnological methods leads to the creation of homozygous genotypes in one generation; therefore a double haploid system is an extremely valuable breeding tool (Wedzony et al, 2009). Plant regeneration in vitro from isolated ovary has been achieved in some crops such as onion (Kamštaitytė, Stanys, 2002), maize (Tang et al, 2006), sugar beet (Gurel et al, 2000), wheat (Sibi et al, 2001). Lately, the overall plant regeneration frequency in flax from anther has been significantly increased by the modification of medium composition (Chen, Dribnenki, 2002;RutkowskaKrause et al, 2003;Burbulis et al, 2005) and culture conditions (Obert et al, 2004 a).…”
Section: Introductionmentioning
confidence: 99%